(untitled) (Revista Rupturas, 2017)
Building upon the contribution of the Latin-American Political Ecology and Critical Geography, we highlight the eco-geo-politics of water from the territories that rise from the practices and discourses of the Movement for the Defense of Water, Land and Environment in the Petorca Province, central zone and its struggle for the reclamation of water. From an ethnographic approach based on interviews with small farmers and an analysis of the water rights granted by the state, we present the struggle for water in Petorca as a historical conflict for the land, which became more radical since the imposition of the water code by the military dictarorship in 1981, and compounded with the expansion of the agro-exportation extractivist frontiers since democracy returned in 1990.